Kebijakan Dividen Perusahaan yang Listing di Bursa Efek Jakarta (BEJ): Besaran, Strategi, dan Stabilitas Dividen - AGUNG GALIH SATWIKO; NACHROWI D. NACHROWI; ADLER HAYMANS MANURUNG (The Indonesian Journal of Accounting Research, 2013)
The objective of this research is to study the dividend policy in the Jakarta Stock Exchange (JSX) in lights of its magnitudes, strategy and stability. The magnitudes will be measured using simple descriptive statistic over 11 years (1992 – 2002) for each sector therein. Meanwhile a dividend payment strategy in conjunction with company’s earnings will be measured using multinomial logistic model. Finally the stability will be measured using Lintner Model (1956), utilizing panel data techniques. The result shows that over the observation periods, sector that pays dividend most out of its earnings is Consumption Goods Industry. On the other hand, sector that pays dividend less out of its earnings is Property and Real Estate. On the strategy side, the result on multinomial logistic model shows that when there is an increase in earnings, decrease in earnings, and negative earnings, most of the firms in JSX will follow the strategy of increasing, decreasing, and omitting dividends, respectively. Finally, using panel data on Lintner Model, firms in JSX generally follow unstable dividend policy, meaning that when there is a change in earnings, it will be immediately followed by a change in dividend payment. This results confirmed previous studies which conclude that firms in developing countries tend to follow an unstable dividend policy, while those in a well developed countries choose a stable dividend policy.